2018
DOI: 10.1002/14651858.cd012472.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Patient-mediated interventions to improve professional practice

Abstract: We found that two types of patient-mediated interventions, patient-reported health information and patient education, probably improve professional practice by increasing healthcare professionals' adherence to recommended clinical practice (moderate-certainty evidence). We consider the effect to be small to moderate. Other patient-mediated interventions, such as patient information may also improve professional practice (low-certainty evidence). Patient decision aids may make little or no difference to the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 187 publications
0
67
0
8
Order By: Relevance
“…The findings of these studies were mixed, with little to no improvements observed for patient-directed or patientmediated strategies when compared to interventions without such components. However, patient-directed [61] and patient-mediated [62,63] interventions have been shown to foster HCP behaviour change and/or patient outcomes in health care settings including cancer care. The contradictory nature of the current review findings may stem from the relatively small number of studies that included patient-directed or patient-mediated strategies as intervention components.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of these studies were mixed, with little to no improvements observed for patient-directed or patientmediated strategies when compared to interventions without such components. However, patient-directed [61] and patient-mediated [62,63] interventions have been shown to foster HCP behaviour change and/or patient outcomes in health care settings including cancer care. The contradictory nature of the current review findings may stem from the relatively small number of studies that included patient-directed or patient-mediated strategies as intervention components.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the comprehensive research translation programme that accompanied the release of the Guideline was to improve the timely and accurate diagnosis and management as well as to augment the consistent implementation of evidence-based care worldwide. A recent Cochrane review demonstrates that obtaining patient-provided information improves adherence with guidelines and evidence-based care [117]. Hence, the Guideline translation encompassed a range of codesigned outputs developed with both women and health professionals, including the freely available and rigorously developed AskPCOS app, which is based on the Guideline and is now used across 112 countries.…”
Section: Translationmentioning
confidence: 99%
“…Few tools exist for eliciting patient priorities and preferences during consultations, including medication reviews [30]. As such, this service might bene t from the introduction of a common framework built on equity, con dence, and perceptions of acceptance [31], for de ning and classifying patient-mediated interventions. Most of the questions associated with medication reviews related to 'structural' elements, i.e.…”
Section: Discussionmentioning
confidence: 99%